Role Of Local Governance In Disaster Management: A Systematic Review - Singh Subhalaxmi Baidhar; Prof. Gyanaranjan Swain; Dr. Banita Mahanandia (Educational Administration: Theory and Practice, 2024)
Research Objective: The main objective of this article is to identify the role of rural local governance in disaster management in India especially in Odisha. Theoretical framework: Rappaport et al., (2018) suggested the use of resilience theory which will help the local governance in disaster management. Within this theory, collaborative governance and partnership methods help understand the relationship between local governance and disaster management. Method: Searching literature helps to understand the use of collaborative governance and partnership methods by rural local governance in disaster management. Through a systematic literature review, there will be the integration of knowledge from past works. Result and Discussion: Through this review article there is the identification of various methods that exist within collaborative governance and partnership methods. Those sub-methods are like “participatory mapping”, and “partnership assessment tools”. Theoretical contribution: The methodologies used in this article help to understand the role of rural local governance in disaster management theoretically. It also targets different contexts to identify the commonalities and differences among those methods. Originality: Through systematic review, this review article will identify the use of collaborative governance and partnership methods by rural local governance in disaster management.